RELATIONSHIP BETWEEN PRIVATE DOMESTIC INVESTMENT AND ECONOMIC GROWTH IN NIGERIA (1986-2018): AUTO-REGRESSIVE DISTRIBUTED LAG APPROACH - Isiaka Kareem JIMBA; Rosemary Bukola AJALA (Malete Journal of Accounting and Finance)
A constant increase in domestic investment has been widely acknowledged as determinant of economic growth. Unfortunately since 1986 till 2018, Nigeria has been recording decline in the domestic investment, a situation that needs urgent attention. This calls for a re-examination of the effect of private domestic investment on economic growth in Nigeria, spanning 1986 to 2018. Upon the threshold of new classical theory of investment, economic growth was proxied by real gross domestic product, while private domestic investment was proxied by gross capital fixed formation. The study incorporated other investment measures like foreign direct investment and public investment into the model, while inflation and exchange rate were taken as control variables. Secondary data was sourced from CBN statistical bulletin of various editions and was estimated using autoregressive distributed lag bound test and its coefficients. The study revealed that private domestic investment and economic growth moves in a long run. It also found that in the short run, GFCF has a negative and significant effect on economic growth, CPCS and EXR have negative and insignificant effects on economic growth, while FDI and INF have positive and insignificant effects on economic growth. In the long run, GFCF has significant and positive effects on economic growth, CPCS, GCE, EXR and INF have positive and insignificant effects on economic growth while FDI has a negative and significant effect on economic growth. The study therefore concluded that private domestic investment has a significant positive effect on economic growth in Nigeria, and all other components of investment positively impacted on economic growth except foreign direct investment. Therefore, the study recommends among others that, government should provide an enabling environment for the private sector to function in order to contribute towards achieving increase in economic growth in Nigeria. The study further recommends policies and strategies that would enhance financial sector development in order to enhance the capacity of Nigerian capital market and banking sector towards providing and allocating necessary funds through accumulated savings for investment needed to achieve sustainable economic growth in Nigeria.